Asymmetric Information and Volatility of Stock Returns in Nigeria - Omokehinde, Joshua Odutola; Abata, Matthew Adeolu; Russell , Olukayode; Migiro, Stephen Oseko; Somoye, Christopher (Journal of Economics and Behavioral Studies, 2017)
This paper investigates the effect of asymmetric information on volatility of stock returns in Nigeria using the best-fit Asymmetric Power Autoregressive Conditional Heteroskedasticity, APARCH (1,1) model, under the Generalized Error Distribution (GED) at 1% significance level from 3 January 2000 to 29 November 2016. The descriptive statistical results showed that the returns were not normally and linearly distributed, with strong evidence of a heteroskedasticity effect. The results of the analysis also confirmed the effect of asymmetric information on the volatility of stock returns in the Nigerian stock market. The asymmetric parameter (γ) was negative at (-1.00), which is statistically significant at 1% level. This confirms that there is an asymmetric or leverage effect where bad news had a more destabilizing effect on the volatility of stock returns than good news. The total impact of bad news on volatility was explosive at 2.0, during the period under review. Also, the volatility persistence which is measured by the sum of ARCH(α) and GARCH(β) stood at 1.695950. This is above unity and suggests that volatility takes a long time to attenuate in Nigeria. This could be largely ascribed to the persistent effect of the 2008 global financial crisis, which probably eroded investors’ confidence in the market.